Molecular characterisation of ERG, ETV1 and PTEN gene loci identifies patients at low and high risk of death from prostate cancer - Reid, Alison; Attard, G.; Ambroisine, L.; Fisher, G.; Kovacs, Gyula; Brewer, D.; Clark, J.; Flohr, P.; Edwards, S.; Berney, D. M.; Foster, C. S.; Fletcher, A.; et al. (British journal of cancer, 2010)
The discovery of ERG/ETV 1 gene rearrangements and PTEN gene loss warrants investigation in a mechanism-based prognostic classification of prostate cancer (PCa). The study objective was to evaluate the potential clinical significance and natural history of different disease categories by combining ERG/ETV 1 gene rearrangements and PTEN gene loss status.